Narrative Identities of Overseas Filipino Domestic Worker Community in Macao (SAR) China - Vargas, Marenel (Archīum Ateneo, 2020)
Domestic workers comprise roughly one-fourth of the total number of overseas Filipino workers (OFWs). They leave the Philippines primarily to provide financial assistance to their families they leave behind. Most of the existing studies investigated the problems they experience at work and with their families. Some studies focused on how they cope with these problems. However, little is known about the narrative identities of this group of labor migrants. This study addresses this gap by identifying the narrative identities of the community of Filipino domestic workers in Macao Special Administrative Region, China. This study utilized qualitative interviews to plot the identities into a three-part timeline: Premigration, during migration, and imagined future. Results show that, before migration, the community of domestic workers identifies as hands-on mothers and inadequate mothers. During migration, work- and family-related identities are present: Modern-day slave, inadequate, fighter, self-sacrificing, employer's family, and hands-on mother. In an imagined future, the community of domestic workers identifies as successful retired OFWs, reconciled life partners, hands-on mothers, and inadequate mothers. Findings highlight the multiple, interacting identities in community narratives and their corresponding effects on experiences. Implications on policies and programs for this labor migrant group are discussed.